Anti-Crisis Approach to the Provision of the Environmental Sustainability of Economy - Popkova, Elena G.; Sergi, Bruno S. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on the notion of the environmental sustainability of the economy. The Sustainable Development Goals, formulated by the UN, led to the formation of a concept of the environmental sustainability of the economy. This concept implies the harmony of economy and environment, achieved due to the support for the SDGs in the economy. This book is original due to its reconsidering the environmental sustainability of the economy from the position of crises. The theoretical significance of the book consists in the development of an anti-crisis approach to the provision of the environmental sustainability of the economy: responsible nature use based on digital markets and smart governance. The proprietary approach allows for the comprehensive description of the potential of the leading technologies-artificial intelligence (AI), robots, the Internet of Things (IoT), and blockchain-to support-during their use in smart governance-crisis management of the environmental sustainability of economy. The book's practical significance is due to the description and detailed discussion of the modern international experience of responsible nature use given the specifics of developed and developing countries. The anti-crisis approach to the provision of the environmental sustainability of the economy is based on digital markets: FinTech, EdTech, GovTech, AgroTech, and EnergyTech, the practice of which is described in the book with the help of multiple examples from the international experience and case studies. The book is aimed at scholars who study environmental economics. In this book, they find an innovative view of the environmental sustainability of the economy in its close connection with economic crises.
Environmental Sustainability of the Agricultural Economy with Reliance on Climate-Smart Agriculture -- Information Risks of the Educational Activities of Universities Under Digitalization -- Mechanisms for Implementing Managerial Innovations at the University -- The Role of Medical Clusters in the Development of NBICS Innovations in Industry 4.0 -- The Prospects for the Development of the Domestic Pharmaceutical Industry in the Context of Import Substitution -- The Lateral Strategy of University Development in the BANI world -- Telemedicine from the Perspective of Social Efficiency -- Digital Transformation of Russian Retail -- Development of the Tourism Industry in the Context of Digital Transformation -- Theoretical Foundations of Organizing and Preparing Schoolchildren for Mathematical Olympiads -- New Needs for the Infrastructure of Entrepreneurship in the Digital Economy Markets and the Prospects for Its Provision -- Contribution of Financial Management to the Digital Competitiveness.
Keywords: International economic integration; Globalization; Political science; Environmental economics; Economic development; Management; Emerging Markets and Globalization; Governance and Government; Environmental Economics; Economic Development, Innovation and Growth; Management